Optimal diagnostic strategy for coronavirus disease 2019 detection in liver transplant recipients: Critical review of available evidence - Michael T Olson; Tania Triantafyllou; Saurabh Singhal (Apollo Medicine)
Liver transplant recipients may face an unusually high risk for coronavirus disease 2019 (COVID-19). Observations of heightened risk, rapid progression of severe complications, greater infectivity, and potential for atypical disease presentations in transplant recipients underscore the critical importance of establishing an early diagnosis. Existing diagnostic approaches are marred by unreasonably high false-negative rates. Given the concerns for false-negative results, we performed a narrative review in effort to compile evidence for and against an optimal diagnostic algorithm for detecting COVID-19 in liver transplant recipients. In this algorithm, patients are triaged according to risk of severe acute respiratory syndrome coronavirus 2 infection. Initial testing is performed with reverse transcriptase-polymerase chain reaction, followed by chest computed tomography after 4 days. Repeat tests are performed as per the risk category, patient status, and urgency of transplant. Liver transplant centers should validate the algorithm presented herein, which is based on existing evidence and designed to maximize patient and provider safety, while assuring accuracy in diagnosis.